Malignant Sternal Tumors: Report of Two Cases - Kharel, Ashish; Shrestha, Shashank; Bhandari, Nikesh; Thakur, Binay (Nepalese Journal of Cancer, 2022)
Primary malignant sternal tumors are rare clinical entities. We came across two such patients with primary sternal tumors. One was a chondroblastic osteosarcoma while the other was a chondrosarcoma. One patient received neoadjuvant chemotherapy followed by surgery. The second patient underwent upfront surgery. Both cases received wide excision of the tumor (sternum along with part of medial ends of bilateral clavicles and upper ribs). Reconstruction was done using autologous bone graft with prolene mesh in one case and titanium reconstruction plates in the other case. Both cases received coverage with pectoralis major muscle flaps.